2006
DOI: 10.1002/adsc.200606077
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Catalytic Properties of Polyaniline‐Supported Metal Complexes

Abstract: Polyaniline-supported Sc, In, Pd, Os and Re catalysts were prepared by using a simple protocol and the thus prepared catalysts were well characterized using FTIR, XPS, UV-Vis/DRS, TGA-DTA. All the catalysts were successfully employed in a wide range of organic transformations such as cyanation and allylation of carbonyl compound, Suzuki coupling of aryl halides and boronic acids, and, most importantly, in asymmetric dihydroxylation of olefins to afford optically active vicinal diols. All the catalysts were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 3 publications
(4 reference statements)
0
29
0
Order By: Relevance
“…[1] When polyaniline (PANI) is used as support, it also functions as reducing agent and stabilizer. These advantages translate into easy and reproducible syntheses that make metal nanoparticles supported by PANI [2,3] promising candidates for organic catalysis. Palladium nanoparticles supported on polyaniline have been the subject of interest of several groups.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[1] When polyaniline (PANI) is used as support, it also functions as reducing agent and stabilizer. These advantages translate into easy and reproducible syntheses that make metal nanoparticles supported by PANI [2,3] promising candidates for organic catalysis. Palladium nanoparticles supported on polyaniline have been the subject of interest of several groups.…”
mentioning
confidence: 98%
“…Palladium nanoparticles supported on polyaniline have been the subject of interest of several groups. [2,3] In general, these nanoparticles are prepared by adding a palladium(II) salt to an aqueous dispersion of PANI. [2] When interfacial polymerization is used for the synthesis of PANI, nanofibers are formed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25,27 Our system is also advantageous because it does not need a phase transfer agent like tetrabutylammonium bromide to help with the hydrophobicity of aryl chlorides. 48,49 At the time of our initial report, we hypothesized that a dissolution and redeposition mechanism was operating. Over the past decade, there have been contradicting claims on the true type of catalysis that takes place with palladium nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…We 47 and others 48,49 previously reported that palladium nanoparticles supported on PANI nanofibers work well for Suzuki coupling in water. In our case, the palladium nanoparticles showed a bimodal distribution with particles of 2 and 50 nm in diameter being present.…”
Section: Introductionmentioning
confidence: 99%